Utilization of Small Dense Low-Density Lipoprotein Cholesterol Testing in Korean Patients Visiting Local Clinics and Hospitals - Choi, Rihwa; Lee, Sang Gon; Lee, Eun Hee (Nutrients, 2022)
Small dense low-density cholesterol (sdLDL) has been the focus of studies due to its potential as an independent risk factor for atherosclerotic cardiovascular diseases. We aimed to investigate the utilization of sdLDL testing by LDL particle size analysis and the prevalence of an sdLDL predominant phenotype in Korean adult patients by visiting local clinics and hospitals. Among 9222 Korean adults (4577 men and 4645 women) with a median age of 62.8 years (interquartile range, IQR 54.5 to 71.8 years) undergoing lipid profile testing using LDL particle size analysis, the prevalence of hypercholesterolemia (total cholesterol ≥ 240 mg/dL), hypo HDL cholesterolemia (<40 mg/dL), and hyper LDL cholesterolemia (≥160 mg/dL) was 7.8%, 12.9%, and 0.5%, respectively. The overall prevalence of the sdLDL predominant non-A phenotype of LDL was 46.8% of study subjects. Approximately 32.8% of the study subjects possessed lipid test results that did not exhibit increased risk except for sdLDL (only the sdLDL predominant non-A phenotype as a risk factor). In Korea, sdLDL testing was utilized in patients whose LDL cholesterol level was not increased. Future studies to clarify the clinical significance of this test in the Korean population are needed.